Hematological and biochemical status of ?eta-thalassemia major patients in Koya city. - Saleh, Kochar Khasro; Kakey, Esmail S. (Salahaddin University - Erbil, 2021)
Thalassemia major is a severe anemia that requires blood transfusions. In this study, we searched into the hematological and biochemical status of ?eta-thalassemia major patients in Koya. Hematological analysis revealed severe anemia in ?eta-thalassemia patients when compared to controls. The hemoglobin levels in patients were less than 30% of that of controls. Furthermore, patients had a significant leukocytosis compared to the controls. Red blood cell incidences are decreased except RDW, which were Hct includes (23.8±2.9 % vs. 34.6±2.3 %), MCV (71.8±7.1 fl vs. 77.5±4.1 fl), MCH (20.2±2.4 pg vs. 23.5 ± 2.2 pg) and MCHC (30.8±0.7 g/dl vs. 30.1±1.2 g/dl), while RDW % (20.5±9.7 % vs. 14.2±2.5 %). The linear regression analysis showed non-correlation between iron overload with RBC, WBC, and red blood cell incidences (hemoglobin (Hb), hematocrit (Hct), mean corpuscle hemoglobin (MCH), and mean corpuscle hemoglobin concentration (MCHC), while PLT count, mean corpuscular volume (MCV) and red cell distribution width (RDW) showed a significant positive correlation with iron overload. The biochemical characteristics of the patients showed a significant increase in the levels of liver enzymatic parameters, ALP, ALT, and AST as compared to controls. © 2021, Salahaddin University - Erbil. All rights reserved.
Keywords: Anemia; Biochemical change; Hematological change; ?eta-thalassemia major